A dual-path mediation model: associations between childhood psychological maltreatment and loneliness among Chinese college students - Zhou, Zihan; Liu, Mingbo; Chen, Liang (Frontiers in Psychiatry, 2026)
ObjectiveThis study aimed to examine the potential psychological mechanisms that may link childhood psychological maltreatment to loneliness among Chinese college students by testing a dual-path mediation model involving trust in others and positive coping styles.MethodsA cross-sectional survey was conducted with 603 college students using self-report measures of childhood psychological maltreatment, trust in others, positive coping styles, and loneliness. Data were analyzed using correlation analysis and structural equation modeling with bootstrapping.ResultsChildhood psychological maltreatment was positively correlated with loneliness and negatively correlated with trust in others and positive coping. Trust in others and positive coping styles were negatively correlated with loneliness. The structural equation model revealed significant indirect effects: childhood maltreatment was associated with loneliness both through reduced trust in others (indirect effect = 0.063, 12.07% of total effect) and through weakened positive coping styles (indirect effect = 0.084, 16.19% of total effect). The total indirect effect accounted for 28.26% of the total variance.ConclusionThe findings support the proposed dual-path model, suggesting that the association between childhood psychological maltreatment and later loneliness may operate through eroded interpersonal trust and impaired development of adaptive coping strategies. This underscores the importance of integrated interventions targeting both trust reconstruction and coping skills training in mitigating the long-term impacts of early adversity.